Effect of calcium ions on rat osseous plate alkaline phosphatase activity - Leone, F. A.; Ciancaglini, P.; Pizauro, J. M. (Elsevier B.V., 1997)
Rat osseous plate alkaline phosphatase is a metalloenzyme with two binding sites for Zn2+ (sites I and III) and one for Mg2+ (site II). This enzyme is stimulated synergistically by Zn2+ and Mg2+ (Ciancaglini et al., 1992) and also by Mn2+ (Leone et al., 1995) and Co2+ (Ciancaglini et al., 1995). This study was aimed to investigate the modulation of enzyme activity by Ca2+. In the absence of Zn2+ and Mg2+, Ca2+ had no effects on the activity of Chelex-treated, Polidocanol-solubilized enzyme. However, in the presence of 10 mu M MgCl2, increasing concentration of Ca2+ were inhibitory, suggesting the displacement of Mg2+ from the magnesium-reconstituted enzyme. For calcium-reconstituted enzyme, Zn2+ concentrations Zip to 0.1 mu M were stimulatory, increasing specific activity from 130 U/mg to about 240 U/mg with a K-0.5 = 8.5 nM. Above 0.1 mu M Zn2+ exerted a strong inhibitory effect and concentrations of Ca2+ up to I mM were not enough to counteract this inhibition, indicating that Ca2+ was easily displaced by Zn2+. At fixed concentrations of Ca2+, increasing concentrations of Mg2+ increased the enzyme specific activity from 472 U/mg to about 547 U/mg, but K-0.5 values were significantly affected (from 4.4 mu M to 38.0 mu M). The synergistic effects observed for the activity of Ca2+ plus magnesium-reconstituted enzyme, suggested that these two ions bind to the different sites. A model to explain the effect of Ca2+ on the activity of the enzyme is presented. (C) 1997 Elsevier B.V.